Implementasi Program Literasi Dalam Meningkatkan Motivasi Belajar Siswa Di UPT SPF SDN Gaddong II Kota Makassar - Rezky Wahyuni; Andi Adam; Besse Syukroni B (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research aims to determine the description of the implementation of the literacy program in increasing student learning motivation at UPT SPF SDN Gaddong II, supporting and inhibiting factors in implementing the literacy program at UPT SPF SDN Gaddomg II. This research uses a qualitative approach with a qualitative descriptive research type. The research objects are students at UPT SPF SDN Gaddong II. The data sources used in this research are observation, interviews and documentation. Data in this research. .Based on the research that has been conducted, the results obtained are (1) an overview of the implementation of literacy programs in increasing student learning motivation at UPT SPF SDN Gaddong II, carried out with several literacy programs such as study quizzes, literacy classes, and library visits. With this literacy program, students are more motivated to learn. This is evident from the students who take part in the literacy program held by the teacher, (2) the supporting and inhibiting factors in implementing the literacy program at UPT SPF SDN Gaddong II are: supporting factors are the cooperation of the principal and teachers, the active role of students and appreciation of the school . while inhibiting factors are internal factors such as family, school environment and psychology, external factors such as society.